2007
DOI: 10.1590/s1413-86702007000400012
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular complications related to HIV infection and highly active antiretroviral therapy

Abstract: With the significant increase in life expectancy for HIV-infected patients in the era of high potency antiretroviral therapy, major metabolic changes have been observed due to the prolonged period of the viral infection and the treatment itself. Osteoarticular changes resulting from these processes are mainly reported in long term HIVinfected patients receiving high potency antiretroviral therapy and include osteopenia/osteoporosis, osteonecrosis, carpal tunnel syndrome and adhesive capsulitis of the shoulder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
(40 reference statements)
0
10
1
1
Order By: Relevance
“…Physical therapists can play an important role in diagnosis and management of the physical dysfunction in HIV-infected patients [34, 35]. This systematic review suggests that concurrent exercise may be an important intervention in the care and treatment of adults living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Physical therapists can play an important role in diagnosis and management of the physical dysfunction in HIV-infected patients [34, 35]. This systematic review suggests that concurrent exercise may be an important intervention in the care and treatment of adults living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…5,13 One explanation for this observation has been the myxedematous accumulation in the carpal tunnel and secondary compression of the median nerve. 12 Asensio et al found no relation between the lipodystrophy secondary to PIs and CTS. 9 The patient did not have the above diseases and has not been receiving HAART when the CTS was diagnosed, therefore, as happened with other published cases, it would be hasty to establish association with HIV infection or HAART.…”
Section: Discussionmentioning
confidence: 96%
“…Many of them, as some occupational activities, hypothyroidism, rheumatoid arthritis and obesity, are also mentioned in HIV-infected individuals. 5,9,12 Clinical observations published by Sclar and Manfredi related CTS with the HAART-associated metabolic syndrome particularly to PIs. 5,13 One explanation for this observation has been the myxedematous accumulation in the carpal tunnel and secondary compression of the median nerve.…”
Section: Discussionmentioning
confidence: 99%
“…11,36 Conditions known to cause avascular necrosis include trauma, alcoholism, infections, medications (including corticosteroids, bisphosphonates, and highly active antiretroviral therapy), dysbaric trauma, marrow infiltration disorders, hypercoagulability states, autoimmune diseases, and idiopathic etiology. 4,27,31 These causes may be divided into three categories: (a) conditions resulting in external blood vessel compression near or within the bone, (b) disorders resulting in blood vessel occlusion because of thickening of the vessel wall, and (c) disorders resulting in blood vessel blockage from a thromboembolic process (Box 11-1). 12 For conditions resulting in external blood vessel compression, the mechanism is either marrow edema causing compression of the vessel in an enclosed region or excessive packing of the marrow through the deposition of abnormal tissue or material (e.g., fat in steroid administration or hyperlipidemia).…”
Section: Avascular Necrosismentioning
confidence: 99%